The Diet Quality Questionnaire (DQQ) Is a Straightforward Data Collection Tool for Assessing Minimum Dietary Diversity for Women (MDD-W) - Olutayo Adeyemi; Muhammad Momoh; Jonathan Makka; Richard Oladipo (Current Developments in Nutrition)
Diet quality is an important cause as well as outcome of food systems and global development challenges. There is an increasing demand for diet quality indicators that can be readily assessed. Traditional methods of assessing diets based on quantitative 24-h dietary recall are time consuming, costly, and require specialized skills. Dietary recall approaches that collect information about the consumption of food groups are growing in popularity as they can be used to compute timely indicators of diet quality at much lower costs. Validated indicators that use this method are also becoming more available. The percentage of women of reproductive age who achieve minimum dietary diversity (MDD-W) of ≥5 of 10 predefined food groups is one such indicator and is a proxy for higher micronutrient adequacy of diets. MDD-W has been adopted as an indicator of the sustainable development goals (SDGs). Valid, feasible, and comparable approaches for collecting data for MDD-W calculation across low-, middle-, and high-income countries are of paramount importance in tracking changes in the indicator. The diet quality questionnaire (DQQ) that uses a sentinel foods, close-ended list-based method offers a reliable approach for collecting and analyzing data for MDD-W. Dairy Development Programs implemented in Nigeria by Sahel Consulting Agriculture and Nutrition Limited have used different methods to collect MDD-W data between September 2017 and December 2024. Methods used have included quantitative 24-h dietary recall, nonquantitative open-recall, open-ended lists, closed-ended extensive lists, and DQQ. Data collection and analysis using DQQ have provided the most cost-effective and time-saving approach to obtaining valid results. DQQ can increase the ability of countries and programs to monitor MDD-W and other diet quality indicators. Low- and middle-income countries like Nigeria may consider integrating the DQQ in national data systems to facilitate reporting on MDD-W for progress tracking toward the SDGs.